Legitimation strategies and discourses in editorials: Myanmar's new foreign policy on ASEAN membership. (April 2021) - Manosuthikit, Aree
Abstract: After decades of military dictatorship, Myanmar finally had its first democratic government in 2015. This political change opened up the opportunity for the country to establish legitimacy as a member of the Association of Southeast Asian Nations (ASEAN). Myanmar newspapers began to publish editorial pages discussing the country's new foreign policy towards ASEAN, including its new roles, stances and engagements with this regional grouping. Using Van Leeuwen's legitimation strategies (2007), his re-contextualization scheme (2008, 2016) and insights on organizational legitimacy in the international organization context (Suchman, 1995; Tallberg and Zürn, 2019; Weber, 1964 ), this interdisciplinary study examines (1) the legitimation strategies employed by Myanmar journalists and (2) the discourses they drew on to justify post-2015 Myanmar's ASEAN membership. The findings reveal that these dual levels of legitimation (strategies and discourses) worked jointly to achieve the editorials' persuasive purpose and, together, produced the following editorial patterns of legitimation: Myanmar's political leader's pledge of solidarity with ASEAN; Myanmar to continue its neutralist stance towards ASEAN; Myanmar to potentially improve ASEAN's democratic profile; Myanmar to bring cooperative security to ASEAN; and Myanmar rewarded with economic opportunities after integrating with ASEAN. The study also offers theoretical recommendations for future research on discursive legitimation in news media.